The consolidation of the islamic studies element in the new structure of general studies in private higher learning institutions in Malaysia: a study on islamic medical institutions - Nazri Muslim; Abdul Latif Samian; Wan Zulkifli Wan Hassan; Nik Yusri Musa; Nur Azuki Yusuff (2013)
The operations of the Private Higher Learning Institutes (IPTS) in Malaysia are under the 1996 Private Study Institutions Act, known as Act 555 carrying the role of supervising, establishing, registering, managing the supervision and control of the quality of education provided by the IPTS. Based on the Allocation of Section 43, all IPTS are required to teach Malaysian Studies and Islamic Studies for Muslim students and Moral Education for non- Muslim students, all of which are known as Compulsory Subjects, or Mata Pelajaran Wajib (MPW). This MPW is compulsory for all students and they must pass these subjects as the condition for them to graduate. Thus, after 15 years of its implementation, the Ministry of Higher Education Malaysia has revised the structure of MPW to General Subjects, or Mata Pelajaran Umum (MPU). Among the aim of the changes that take place is to improve selfpotential among students, towards producing holistic students and for both the IPTA and IPTS to have a common feature. This purpose is met, through philosophical understanding, the comprehension over values and history, the mastery of human skills, the broadening of knowledge in Malaysia and the applications of human skills. Thus, this paper seeks to discuss the element of Islamic studies in the MPU’s new structure. The outcome of the discussion suggests that the element of Islamic studies has been instilled in MPU more extensively towards producing students who understand good noble values and self-identity by making reference to the Islamic Medical Institutions.